2021
DOI: 10.1002/anie.202102339
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Site vs. Cluster Catalysis in High Temperature Oxidations

Abstract: The behavior of single Pt atoms and small Pt clusters was investigated for high‐temperature oxidations. The high stability of these molecular sites in CHA is a key to intrinsic structure–performance descriptions of elemental steps such as O2 dissociation, and subsequent oxidation catalysis. Subtle changes in the atomic structure of Pt are responsible for drastic changes in performance driven by specific gas/metal/support interactions. Whereas single Pt atoms and Pt clusters (> ca. 1 nm) are unable to activate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 71 publications
0
32
0
2
Order By: Relevance
“…Recent reports pointed out that the coexistence of oxidic and metallic Pt species played a key role in enhancing the low-temperature catalytic activity, in which the oxidized Pt phase provided active oxygen while metallic Pt species supplied optimal adsorption sites for CO. Serna et al reported that CO molecules can facilitate the consolidation of Pt atoms through reduction of active sites under applied conditions such as CO oxidation . In other words, oxygen vacancies induced by the consumption of active lattice oxygen to react with CO might push the transformation of ionic Pt species to a dual oxidic-metallic Pt phase.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recent reports pointed out that the coexistence of oxidic and metallic Pt species played a key role in enhancing the low-temperature catalytic activity, in which the oxidized Pt phase provided active oxygen while metallic Pt species supplied optimal adsorption sites for CO. Serna et al reported that CO molecules can facilitate the consolidation of Pt atoms through reduction of active sites under applied conditions such as CO oxidation . In other words, oxygen vacancies induced by the consumption of active lattice oxygen to react with CO might push the transformation of ionic Pt species to a dual oxidic-metallic Pt phase.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Similar importance bear zeolite supports which are capable of hosting and stabilizing single atoms to well-defined ultrasmall clusters and have been characterized by a variety of techniques, 36–48 including zeolites in 2D 49 and 1D 50 form.…”
Section: Structure and Reshapingmentioning
confidence: 99%
“…A variety of coordinated metal clusters with special structures can be obtained by designing organic ligands and changing the inorganic metal nodes, giving varied functions, 34–36 such as luminescence, magnetism, catalysis, etc. 37–58 Among them, LCMCs have been widely used in the detection of metal ions, nitro explosives and biomolecules because of their well-defined active sites, accurately tailorable structures and excellent luminescent properties, enabling mechanism-based luminescence sensing optimization. 59–65 According to literature studies, there are few reports using LCMCs as luminescence sensors for detecting halide ions or amino acids, especially no bifunctional sensors for halide ions and amino acid determination.…”
Section: Introductionmentioning
confidence: 99%